Alpha 1-antitrypsin mitigates salt-sensitive hypertension in juvenile mice by reducing diacylglycerol concentrations and protein kinase C activity in kidney membranes - Dogan, Yunus E.; Bala, Niharika; Galban, Erika S.; Lewis, Russell L.; Denslow, Nancy D.; Song, Sihong; Alli, Abdel A. (Frontiers in Molecular Biosciences, 2025)
IntroductionRecombinant alpha-1 antitrypsin (AAT) therapy has been shown to have beneficial effects to mitigate the progression of various diseases. Here, we hypothesized that administration of pharmaceutical-grade human AAT (hAAT) is effective in mitigating hypertension induced by salt-loading in juvenile mice by reducing the concentration of diacylglycerols (DAGs) and activity of protein kinase C (PKC) in the kidney.MethodsFour-week old 129Sv mice were salt-loaded to induce hypertension and then administered hAAT or vehicle.ResultsAdministration of hAAT was found to significantly reduce high blood pressure in both the active and inactive cycles of the 129Sv hypertensive mice. A lipidomic analysis showed decreased concentrations of multiple diacylglycerols in kidney cortex membrane fractions from mice treated with hAAT compared to vehicle. PKC activity was less in the 129Sv mice that received hAAT compared to vehicle. Western blotting and immunohistochemistry analysis showed the density of the sodium-potassium-chloride co-transporter (NKCC2) was significantly reduced in kidney cortex membrane fractions of juvenile mice that received hAAT compared to vehicle.ConclusionTaken together, this study demonstrates a new protective effect of hAAT in normalizing blood pressure after the development of saltinduced hypertension in juvenile mice in a mechanism involving a decrease in NKCC2 membrane expression, presumably due to decreased levels of DAGs in the plasma membrane and a subsequent decrease in PKC activity.